POLA ASUH ORANG TUA TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT TERHADAP KARIES GIGI MOLAR 1 PADA SISWA/I KELAS II SD NEGERI 106146 MULIOREJO KECAMATAN MEDAN SUNGGAL - SIMAREMARE, ASNITA BUNGARIA; Sondang; Rosdiana Tiurlan Simaremare; Nissa Alya Sabina (Poltekkes Kemenkes Medan, 2025)
Maintaining children's dental and oral health from an early age is an important practice for parents to implement, serving as role models for their children to develop awareness about dental hygiene. Parental parenting patterns can be carried out by educating and guiding children on how to maintain their dental health and encouraging them to incorporate dental care into their daily routines.This study used a descriptive survey method with a sample of 32 participants. The purpose of this research is to determine the parenting patterns regarding dental health maintenance in relation to first molar dental caries among Grade II students of SD Negeri 106146 Muliorejo, Medan Sunggal District.The results showed that the level of parental parenting regarding dental and oral health related to first molar dental caries among the Grade II students of SD Negeri 106146 Muliorejo, Medan Sunggal District was in the